ANALISIS GESER BALOK-T BETON BERTULANG BERLUBANG MEMANJANG DENGAN MENGGUNAKAN METODE ELEMEN HINGGA NONLINIER - Saleh Nur, Kasmat (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT The presence of flanges on the reinforced concrete T-beam increases the shear capacity, but if the beam-T is made in hollow elongated affect shear capacity. This research conducted to find numerical modelling of nonlinear finite element for hollow reinforced concrete. using the program ATENA V.2.1.10 which were then verified with numerical experiment model. The results showed that the hole in hollow reinforced concrete is not enough affect the shear capacity but may reduce the ductility, in which the ductility decreases as the ratio of the hole increases. Keywords : Reinforcement concrete, Hollow core beam, Shear, Ductility, Crack pattern.